Development of Math Counting Box to Improve Students’ Numeracy Skill in Phase A - Tasya Putri Rahmadani; Diana Endah Handayani; Iin Purnamasari (Journal of Education Technology, 2025)
Numeracy skills among early-grade students remain relatively low, particularly in mastering the concepts of addition and subtraction. This issue is exacerbated by the lack of interactive and developmentally appropriate learning media that can provide meaningful learning experiences. This study aims to develop and evaluate the effectiveness of the Math Counting Box as a learning medium to enhance students’ numeracy skills. The research employed a Research and Development (R&D) method using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were lower-grade elementary school students. Data collection involved expert validation, numeracy tests through pretest and posttest, and student response questionnaires. The instruments used included validation sheets, numeracy test items, and a Likert-scale questionnaire. Data were analyzed using a paired sample t-test to determine the effect of the media on learning outcomes. The results showed that the Math Counting Box demonstrated a high level of validity, significantly improved numeracy scores (p < 0.001), and received very positive responses from students with an average rating of 89.72%. These findings indicate that the media is effective in enhancing basic numeracy skills and can serve as an innovative solution to support mathematical thinking development at an early educational stage.